THE EFFECT OF SYNTHETIC DRUGS USED FOR THE DISEASE OF THE BLOOD PRESSURE ON HUMAN BODY (Scientific journal of the Fergana State University, 2023)
The article discusses the chemical composition of synthetic drugs used in the treatment of arterial hypertension, and their negative impact on other organs in the human body .The chemical composition of ziziphora was studied and compared with the chemical composition of synthetic drugs. Ziziphora has been found to actually help lower blood pressure because of its similarity to the chemical composition of synthetic drugs.Conclusions are drawn on the creation of a food supplement product based on the ziziphora plant